Trinuclear PdII Complexes with a C3‐Symmetric Triethynylbenzene‐Based Tris‐NHC Ligand: Catalytic Benefits - Mondal, Bhaskar; Naskar, Rajat; Dey, Aditya; Sinha, Narayan; Hahn, F. Ekkehardt; Maity, Ramananda (Chemistry : a European journal, 2023)
A new C3‐symmetric tris‐imidazolium tribromide salt 3, featuring 1,3,5‐substituted triethynylbenzene, was used for the preparation of a trinuclear PdII pyridine‐enhanced precatalyst preparation stabilization and initiation‐type (PEPPSI) complex by triple C2 deprotonation followed by the addition of PdCl2. Trinuclear PdII complex possessing a combination of NHC and PPh3 ligands has also been synthesized. The corresponding mononuclear palladium(II) complexes have also been synthesized for the comparison purpose. All these complexes have been characterized by using NMR spectroscopy and ESI mass spectrometry. The molecular structure of the trinuclear palladium(II) complex bearing mixed carbene and pyridine donor ligands has been established by using single crystal XRD. All the palladium(II) complexes have been used as pre‐catalysts, which gave good to excellent yields in intermolecular α‐arylation of 1‐methyl‐2‐oxindole and Sonogashira coupling reaction. Catalytic studies indicate an enhanced activity of the trinuclear PdII complex in comparison to the corresponding mononuclear PdII complex for both catalytic transformations. The better performance of the trinuclear complex has also been further supported by preliminary electrochemical measurements. A negative mercury poison test was observed for both the aforementioned catalyses and therefore, it is likely that these organic transformations proceed homogeneously. Catalytic benefits: Trinuclear PdII complexes with an extended C3‐symmetric triethynylbenzene‐based tris‐NHC ligand are presented. Catalytic studies indicate an enhanced activity of the trinuclear PdII complex in comparison to the corresponding mononuclear PdII complex. An electronic effect in the trinuclear ligand platform is likely to be responsible for the better catalytic activity of the trinuclear complexes over mononuclear complexes.